2020
DOI: 10.1002/micr.30555
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thymus transplantation on donor‐specific chimerism in the rat model of composite osseomusculocutaneous sternum, ribs, thymus, pectoralis muscles, and skin allotransplantation

Abstract: IntroductionResearch on tolerance has proven that development of donor‐specific chimerism (DSC) may accompany tolerance induction in vascularized composite allotransplantation (VCA). In this study, we aimed to determine the effect of thymus transplantation on the induction of DSC in rat VCA model of osseomusculocutaneous sternum (OMCS) and osseomusculocutaneous sternum and thymus (OMCST) allotransplantation.Materials and MethodsA total of 20 Lewis‐Brown Norway and Lewis rats, 5–6 weeks old, weighting between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…These findings may provide foundation for the possible mechanism of action of DRCC in vivo, showing immunomodulatory effects, thus altering the T cell repertoire by presenting mixed antigens on DRCC surface and/or acting as cells stimulating the regulatory cells via cytokine signaling. Studies in solid organs, VCA and BMT reported migration of donor-derived cells to the recipient’s lymphoid tissues and organs as well as lungs, skin and liver and confirmed their role in tolerance induction process (Khan et al 1996 ; Ozmen et al 2006b ; Siemionow et al 2006 ; Zor et al 2020 ). Both thymus and spleen are considered as immune cell rich organs participating in innate and adaptive immune response (Dor et al 2003 ; Gagliani et al 2013 ).…”
Section: Discussionmentioning
confidence: 94%
“…These findings may provide foundation for the possible mechanism of action of DRCC in vivo, showing immunomodulatory effects, thus altering the T cell repertoire by presenting mixed antigens on DRCC surface and/or acting as cells stimulating the regulatory cells via cytokine signaling. Studies in solid organs, VCA and BMT reported migration of donor-derived cells to the recipient’s lymphoid tissues and organs as well as lungs, skin and liver and confirmed their role in tolerance induction process (Khan et al 1996 ; Ozmen et al 2006b ; Siemionow et al 2006 ; Zor et al 2020 ). Both thymus and spleen are considered as immune cell rich organs participating in innate and adaptive immune response (Dor et al 2003 ; Gagliani et al 2013 ).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, there is an urgent need to develop new, cell-based therapies, which will extend allograft survival without the need for harmful conditioning protocols or life-long immunosuppression. New stem cell strategies are based on the tailored, customized approaches to address the individual patient needs and to change the current paradigm To address these limitations, for the past 20 years, our Laboratory has developed novel protocols for induction of tolerance via establishment of donor specific chimerism tested in different experimental models of VCA, including limb allograft transplant carrying vascularized BM component (8)(9)(10)(11)(12)(13)(14)(15). Based on this experience confirming a crucial role of the vascularized BM component of donor origin in induction of donor specific chimerism, we have created DRCC via PEG-mediated fusion of BM cells derived from two unrelated donors (13).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has over 20 years of research experience in chimerism induction and application of BM-based cell therapies in different VCA models (8)(9)(10)(11)(12)(13)(14)(15). These pioneering studies on tolerance induction in VCA encouraged us to create the donor-recipient chimeric cells (DRCC) via ex vivo, polyethylene glycol (PEG)-mediated fusion.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, our previous study proved that less donor-reactive Vβ5-expressing CD4 + T cells were detected in tolerant recipients, hence suggesting the role of thymus in central tolerance ( 38 ). Moreover, donor-specific chimerism was diminished in VCA recipients with thymectomy ( 43 45 ). The pilot data regarding engineered donor–recipient hybrid thymus were reported have potential to promote a dominant regulation of alloreactivity to achieve allograft tolerance ( 46 ).…”
Section: Discussionmentioning
confidence: 99%